Antioxidant Activity, Sun Protection Activity, and Phytochemical Profile of Ethanolic Extracts of Daemonorops acehensis Resin and Its Phytosomes - Rita Kartika Sari; Yanico Hadi Prayogo; Salman Arib Rozan; Mohamad Rafi; Ietje Wientarsih (MDPI AG, 2022)
Daemonorops (Indonesian: jernang) resin is one of Indonesia's leading non-timber forest products and can be developed as a source of natural antioxidants and sun protection. This study aimed to select promising solvents for extracting a Daemonorops acehensis resin and phytosome formulation with high antioxidant capacities and sun protection factor (SPF) values. Jernang resin was extracted using a water-ethanol mixture in five different ratios. The promising extract was then mixed with soy lecithin in three different formulations. A promising extract and phytosome were then selected based on their antioxidant capacities and sun protection factor (SPF) values. A liquid chromatography mass spectrometry/mass spectrometry (LC-MS/MS) analysis was also performed on five extracts to identify the components in the extracts that might be responsible for the biological activity. The results showed that the ethanol solvent variation and phytosome formulation influenced the antioxidant capacity and SPF value. A hundred-percent ethanolic extract and F1 phytosome exhibited the highest antioxidant capacities and SPF values. A qualitative analysis revealed the various classes of compounds in the extract and phytosome. A flavylium chromophore, dracorhodin, dominated the resin extract and was presumed to be the marker compound responsible for their antioxidant capabilities and SPF values. These findings are important for manufacturing sunscreens containing active compounds of bioactive natural resins.